Analisis Kualitatif Belanja Pertanian Terhadap Kesejahteraan Petani dan Ekonomi Inklusif Deli Serdang - Rangkuti, Agus Edy; Supriana, Tavi; Lindawati, Lindawati; Ayu, Sri Fajar (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study examines the impact of government agricultural expenditure on farmers’ welfare and inclusive economic growth in Deli Serdang Regency, North Sumatra, using a qualitative approach. The research aims to understand farmers’ perceptions of government programs, analyze how implementation mechanisms influence social and economic dynamics, and evaluate their contribution to inclusive growth. Data were collected through in-depth semi-structured interviews with 12 informants, field observations, and document analysis, using thematic analysis for data interpretation. While previous quantitative studies have shown a positive correlation between government support and farmers’ welfare, this research reveals a significant gap between policy intentions and on-the-ground reality. Findings indicate that while subsidies provide direct benefits in reducing production costs, aid distribution is often inefficient and poorly targeted due to the role of informal "gatekeepers" within farmer groups. This creates social friction and fosters a cycle of dependency, where planting schedules are dictated by aid disbursement rather than optimal seasonal cycles. The study concludes that the effectiveness of government spending is not determined by the amount allocated but by the fairness, transparency, and quality of its implementation. Achieving truly inclusive growth requires a shift from charity-based assistance to capacity-building empowerment and differentiated programs based on specific agro-ecological zones.